Radiation effects on MHD boundary layer flow and heat transfer over a nonlinear stretching surface with variable wall temperature in the presence of non-uniform heat source/sink - Raj, Wilfred Samuel J.; Agneeshwari, M.; Anjali Devi, S.P. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, an investigation is made to analyze the effects of radiation on an MHD boundary layer flow and heat transfer over a nonlinear stretching surface with variable wall temperature and non-uniform heat source/sink. A suitable similarity transformation is used to transform the governing nonlinear partial differential equations into a system of nonlinear ordinary differential equations by using the Nachtsheim Swigert shooting iteration technique together with the fourth order Runge Kutta method.
Keywords: MHD; radiation; non-uniform heat source/sink; variable wall temperature